A computing model for improving marketable quality and profitability of corporations. (26th May 2009) - Barolli, Valbona; Fukuda, Heihachiro; Barolli, Leonard; Takizawa, Makoto
In this paper, we provide an evaluation model for marketable quality and profitability of corporations. We apply the real values of some leading manufacturing corporations in Japan to our proposed model to analyse its accuracy. From the analysis, we concluded that the theoretical and real standard values of the marketable quality indicator were both 0.6. We showed that the proposed model gives a good approximation of economic trends of Japanese corporations. We obtained a general distribution of profitability by using the general profitability function and the marketable quality indicator. The general distribution is closer to the real value compared with the standard distribution.